Performance of improved versions of Swarna introgressed with yield enhancing genes in multi-location trials - Kousik, M.B.V.N.; Punniakotti, E.; Rekha, G.; Chaitra, K.; Harika, G.; Dilip, T.; Hajira, S.K.; Swapnil, R.K.; Laxmi Prasanna, B.; Mastanbee, S.K.; Anila, M.; Ayyappa Dass, M.; et al. (Association of Rice Research Workers, 2023)
Swarna (MTU7029), an Indian mega-variety of rice, is cultivated on an estimated 8Mha of land. There is a pressing need to address yield stagnation and wider adaptability to irrigated lowland and rainfed ecologies as a result of the negative consequences of climate change and population growth. The present study was aimed at improving Swarna for two yield-related traits through marker-assisted backcross breeding strategy by introgression of OsSPL14 (panicle branching) and SCM2 (stronger culm). Foreground and background selection was carried out at each generation. Homozygous BC2F2 plants harbouring both yield-enhancing genes were identified and advanced through pedigree selection till BC2F5 and evaluated in station trials. Three promising lines possessing higher yield over recurrent parent were identified, and a single line, IET 27661 exhibited superior yield in multi-location trials of the All India Coordinated Rice Improvement Programme (AICRIP) and was found to be promising.